Variation of wind speed distribution characteristics across Indian sub-continent. (2018) - Kiplangat, D.C.; Drisya, G.V.; Asokan, K.; Kumar, K. Satheesh
Knowledge of wind speed and its characteristics is important for the optimising the production and transmission of wind power generated by wind mills. In this paper, we analyse the frequency component level distribution characteristics of wind speed variations at the locations across Indian sub-continent. The results show significant variation of the distribution behaviour among frequency components. We also analyse effect of location, seasonal variation and temporal position in the solar cycle. The skewness and kurtosis show clear scaling behaviour against latitude showing a decrease as location approaches equator. The impact of solar cycle is more predominant at the locations closer to the equator. The seasonal impact on distribution characteristics is also the evident and more prominent at the locations closer to the equator in solar maximum year.